Humidification Performance of Heat and Moisture Exchangers for Pediatric Use. (15th November 2011) - Chikata, Yusuke; Sumida, Chihiro; Oto, Jun; Imanaka, Hideaki; Nishimura, Masaji
Abstract : Background . While heat and moisture exchangers (HMEs) have been increasingly used for humidification during mechanical ventilation, the efficacy of pediatric HMEs has not yet been fully evaluated. Methods . We tested ten pediatric HMEs when mechanically ventilating a model lung at respiratory rates of 20 and 30 breaths/min and pressure control of 10, 15, and 20 cmH2 O. The expiratory gas passed through a heated humidifier. We created two rates of leakage: 3.2 L/min (small) and 5.1 L/min (large) when pressure was 10 cmH2 O. We measured absolute humidity (AH) at the Y-piece. Results . Without leakage, eight of ten HMEs maintained AH at more than 30 mg/L. With the small leak, AH decreased below 30 mg/L (26.6 to 29.5 mg/L), decreasing further (19.7 to 27.3 mg/L) with the large leak. Respiratory rate and pressure control level did not affect AH values. Conclusions . Pediatric HMEs provide adequate humidification performance when leakage is absent.